The influence of prosocial motivation on youth entrepreneurs wellbeing - Tahmid, Ahnaf (2020)
The business world is changing rapidly and with that, the relationship between business and society has been evolving too. This transformation is causing classic definitional blur between the private and non-profit sector. Increasing tensions and paradoxes that affects the wellbeing of entrepreneurs dwelling in this changing environment. Global youth population is at its peak and youth’s participation in entrepreneurship has increased compare to previous times. The transformation within the business environment puts youth’s wellbeing in a vulnerable position. Although previous literature addressed entrepreneurs’ wellbeing, limited knowledge exists when it comes to understanding youth entrepreneurs’ wellbeing. Especially with the transforming business environment where enterprises are adopting prosocial goals, that creates a gap in the entrepreneurship literature. The study of wellbeing in entrepreneurship has started to gain prominence. At the same time, the interest in exploring relationship between motivation and entrepreneurs’ wellbeing is increasing. So far, entrepreneurship research has outlined the positive impact on wellbeing and in most cases, the research focused on social entrepreneurs. However, recent studies show that commercial entrepreneurs can have prosocial motivation and there may be a harmful side of having prosocial motivation. This dissertation takes a qualitative approach in exploring prosocial motivation of both social and commercial entrepreneurs and understand the effects of having such motivation on their wellbeing. In psychological wellbeing, there are two dimensions- hedonic and eudaimonic wellbeing. Most entrepreneurship study on wellbeing emphasized on the hedonic approach, which according to many scholars systematically neglects important aspects of psychological wellbeing. Therefore, this study aims to understand how entrepreneurs cultivate both forms of wellbeing, with emphasis given on understanding prosocial motivations effect on eudaimonic wellbeing as it covers multiple facets of psychology.